Abraham Flexner papers - Flexner, Abraham, 1866-1959.; Pritchett, Henry S. (Henry Smith), 1857-1939.
Correspondence, research material for Flexner's work, "Medical Education in the United States and Canada" (1910), reports, notes, family papers, clippings, printed material, and other papers pertaining chiefly to Flexner's activities in educational reform. Documents his work with the Carnegie Foundation for the Advancement of Teaching and other foundations to expand research and educational opportunities and his service as secretary of the General Education Board. Includes Henry S. Pritchett's correspondence during his service on the U.S. Light-House Board.
Family correspondents include his wife Anne Crawford Flexner, daughters Jean Atherton Flexner and Eleanor Flexner, Bernard Flexner, Hortense Flexner, and James Thomas Flexner. Other correspondents include Louis Bamberger, John D. Barrett, E. Michael Bluestone, Welles Bosworth, W. R. Boyd, Wallace Buttrick, Huntington Cairns, Evans Clark, Richard Courant, Thomas Stephen Cullen, Harold W. Dodds, Albert Einstein, Raymond Blaine Fosdick, Robert J. Getty, Jean Gottmann, Paul H. Hanus, Caryl Parker Haskins, James Hazen Hyde, William S. Learned, Herbert H. Lehman, Charles A. Lindbergh, E. A. Lowe, Paul Mantoux, Violet R. Markham, Thomas H. McKittrick, Paul Mellon, Benjamin Dean Meritt, Allan Nevins, John D. Rockefeller (1874-1960), Julius Rosenwald, Lessing J. Rosenwald, Dean Rusk, Ellery Sedgwick, William Henry Welch, Hermann Weyl, Sir E. L. Woodward, and the Ford Foundation.
Author and educational reformer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bamberger, Louis, -- 1855-1944 -- Correspondence; Barrett, John D., -- 1903-1981 -- Correspondence; Bluestone, E. Michael -- 1891-1979 -- Correspondence; Bosworth, Welles, -- 1869-1966 -- Correspondence; Boyd, W. R. -- 1864-1950 -- Correspondence; Buttrick, Wallace, -- 1853-1926 -- Correspondence; Cairns, Huntington, -- 1904-1985 -- Correspondence; Clark, Evans, -- 1888-1970 -- Correspondence; Courant, Richard, -- 1888-1972 -- Correspondence; Cullen, Thomas Stephen, -- 1868-1953 -- Correspondence; Dodds, Harold W. -- 1889-1980 -- Correspondence; Einstein, Albert, -- 1879-1955 -- Correspondence; Flexner, Anne Crawford, -- 1874-1955 -- Correspondence; Flexner, Bernard, -- 1865-1945 -- Correspondence; Flexner, Eleanor, -- 1908-1995 -- Correspondence; Flexner, Hortense, -- 1885-1973 -- Correspondence; Flexner, James Thomas, -- 1908-2003 -- Correspondence; Flexner, Jean Atherton -- Correspondence; Fosdick, Raymond B. -- 1883-1972 -- Correspondence; Getty, Robert J. -- Correspondence; Gottmann, Jean -- Correspondence; Hanus, Paul H. -- 1855-1941 -- Correspondence; Haskins, Caryl P. -- 1908-2001 -- Correspondence; Hyde, James H. -- 1876-1959 -- Correspondence; Learned, William S. -- 1876-1950 -- Correspondence; Lehman, Herbert H. -- 1878-1963 -- Correspondence; Lindbergh, Charles A. -- 1902-1974 -- Correspondence; Lowe, E. A. -- 1879-1969 -- Correspondence; Mantoux, Paul, -- 1877-1956 -- Correspondence; Markham, Violet R. -- Correspondence; McKittrick, Thomas H. -- 1889-1970 -- Correspondence; Mellon, Paul -- Correspondence; Meritt, Benjamin Dean, -- 1899-1989 -- Correspondence; Nevins, Allan, -- 1890-1971 -- Correspondence; Rockefeller, John D., -- Jr. -- 1874-1960 -- Correspondence; Rosenwald, Julius, -- 1862-1932 -- Correspondence; Rosenwald, Lessing J. -- 1891-1979 -- Correspondence; Rusk, Dean, -- 1909-1994 -- Correspondence; Sedgwick, Ellery, -- 1872-1960 -- Correspondence; Welch, William Henry, -- 1850-1934 -- Correspondence; Weyl, Hermann, -- 1885-1955 -- Correspondence; Woodward, E. L. -- 1890-1971 -- Correspondence; United States. -- Light-House Board; Carnegie Foundation for the Advancement of Teaching; Ford Foundation -- Correspondence; General Education Board (New York, N.Y.); Education; Educational change; Medical education -- Canada; Medical education -- United States; Research; Authors; Educators; Reformers